ISSUES OF DEVELOPING CATERING OUTSOURCING SERVICES - Ergasheva Nasiba , Rakhmatullaevna (THE INNOVATION ECONOMY, 2025)
this article presents scientifically based proposals and recommendations on the priority areas of scientific research in this area, such as modern forms of organizing catering outsourcing services in economic sectors, the main trends in the global catering outsourcing services market and its geography, the importance, structure and specific characteristics of enterprises and organizations, criteria for qualitative assessment of the provision of all sectors, directions for the development of catering outsourcing services, innovative approaches to organizing catering and the use of digital technologies.